A Nutritional supplementation intervention with coenzime Q10, Tryptophan and Magnesium for the management of Fibromyalgia symptoms - Gómez-Centeno, Antonio; Ramentol, Mercedes; González, Maria J.; Alegre, Cayetano (Progress in Nutrition, 2021)
Introduction and Objectives: Management of fibromyalgia syndrome (FMS) is challenging and requires a multidisciplinary strategy. This pilot study aimed to investigate the effects of a dietary supplementation (NSC) containing coenzyme Q10, magnesium and tryptophan on reducing fibromyalgia symptoms, and to assess its tolerability. Materials and methods: Patients underwent a 3 month-treatment with NSC followed by 1-month washout and 3 month-treatment with placebo. The Combined Index of Severity of Fibromyalgia (ICAF) was used to evaluate FMS main symptoms. Results: Twenty women completed the study, with a mean age of 51.9 (±7.2) years. Mean time since experiencing fibromyalgia symptoms was 7.7 (±6.3) years. Depression and anxiety were reported in 65.0% (13/20) and 30.0% (6/20) of cases, respectively. Fatigue and functional capacity improved after both treatment periods, whereas pain, sleep quality and impact enhanced only after NSC intake. Depression, anxiety symptoms and patients’ general health did not improve after treatment. Active coping strategies enhanced after study treatment (not after placebo treatment), while passive coping strategies worsened (even more after placebo treatment). The global ICAF improved after NSC treatment and declined after placebo treatment. No significant differences were found in any of the efficacy outcomes. NSC treatment was well tolerated, with a low incidence of adverse events (5.0%, 1/20). Discussion and Conclusions: Supplementation with NSC was effective in improving physical aspects of FMS such as fatigue, pain, sleep quality and functional capacity, as well as global well-being of patients. However, larger studies are needed to confirm the results of this pilot study and whether improvements observed could be statistically significant.